Expression and localization of SWEETs in Populus and the effect of SWEET7 overexpression in secondary growth. (4th November 2020) - Zhang, Li; Wang, Lijuan; Zhang, Jin; Song, Cai; Li, Yu; Li, Jianbo; Lu, Mengzhu
Abstract: In trees, wood formation needs carbon import from the photosynthetic source tissues. Sugar transporters play important roles in carbohydrate transport into wood-forming cells. Sugars will eventually be exported transporters (SWEETs) play essential roles in many physiological processes. However, the roles of this family in the growth and development of woody plants have not been systematically investigated. In this study, 27 SWEET genes were identified in the Populus trichocarpa genome. These SWEET genes were classified into four clades based on their phylogenetic relationships, gene structures, conserved motifs and chromosomal locations. Representative SWEET members from each clade were selected for further studies. The PagSWEETs of Populus alba × Populus glandulosa were localized to plasma membrane, vacuolar, endoplasmic reticulum or Golgi. Quantitative real-time reverse transcription polymerase chain reaction (qRT-PCR) analysis showed that PagSWEETs have distinct expression patterns in various tissues, and PagSWEET5, 7, 10b, 10c, 15b, 17a and 17c exhibited high expression levels in stems. PagSWEET7 is localized to the cytoplasmic membrane and specifically expressed in the phloem as detected by histochemical GUS (β - glucuronidase) assays. Xylem production and xylem sugar content were greater in developing wood of PagSWEET7 overexpression than wild-type lines. Collectively, these results provide valuable information for further investigating functions of PagSWEET genes, and identify PagSWEET7 as a candidate gene for using biotechnology to modify the wood formation in poplar.